Online Postgraduate Course Registration and Payment System at FSKTM / See Chuan Kiat - See, Chuan Kiat (2002)
An Online Postgraduate Course Registration and Payment System is developed for postgraduate students in the Faculty of Computer Science and Information Technology (FSKTM), University of Malaya (UM). It is a Web application development. The system is developed to facilitate student online course registration and payment of fees. The system overcomes the queuing problem during the course registration and fees payment. UM administrators can view, delete and update the course registration, student, and administrative record through the system. ASP (Active Server Pages) is used to develop the system. Microsoft Access 2000 is used to store the student database.